An automatic framework for fusing information from differently stained consecutive digital whole slide images: A case study in renal histology. (September 2021) - Merveille, Odyssee; Lampert, Thomas; Schmitz, Jessica; Forestier, Germain; Feuerhake, Friedrich; Wemmert, Cédric
Highlights: Design of a pipeline to analyse glomeruli in consecutive whole slide images with different stainings. Development of a matching algorithm to follow the same glomeruli through consecutive slices. Proposal of several features to analyse the glomeruli micro-environment. Abstract: Objective: This article presents an automatic image processing framework to extract quantitative high-level information describing the micro-environment of glomeruli in consecutive whole slide images (WSIs) processed with different staining modalities of patients with chronic kidney rejection after kidney transplantation. Methods: This four-step framework consists of: 1) approximate rigid registration, 2) cell and anatomical structure segmentation 3) fusion of information from different stainings using a newly developed registration algorithm 4) feature extraction. Results: Each step of the framework is validated independently both quantitatively and qualitatively by pathologists. An illustration of the different types of features that can be extracted is presented. Conclusion: The proposed generic framework allows for the analysis of the micro-environment surrounding large structures that can be segmented (either manually or automatically). It is independent of the segmentation approach and is therefore applicable to a variety of biomedical research questions. Significance: Chronic tissue remodelling processes after kidney transplantation can result in interstitial fibrosis and tubular atrophy (IFTA) and glomerulosclerosis. This pipeline provides tools to quantitatively analyse, in the same spatial context, information from different consecutive WSIs and help researchers understand the complex underlying mechanisms leading to IFTA and glomerulosclerosis.